2002
DOI: 10.1161/01.cir.0000035655.45453.d2
|View full text |Cite
|
Sign up to set email alerts
|

Association of Angiotensin-Converting Enzyme With Low-Density Lipoprotein in Aortic Valvular Lesions and in Human Plasma

Abstract: Background-Recent studies have demonstrated that lesions of aortic sclerosis and stenosis share several similarities with lesions of atherosclerosis. In atherosclerosis, angiotensin-converting enzyme (ACE) is expressed by a subset of macrophages. This study was undertaken to determine whether ACE might be present in aortic sclerosis or stenosis lesions. Methods and Results-Immunohistochemistry was performed on 26 paraffin-embedded human aortic valves. Monospecific antibodies were used to identify ACE, macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
179
0
21

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 272 publications
(207 citation statements)
references
References 35 publications
7
179
0
21
Order By: Relevance
“…Lipoproteins and inflammatory cells, such as macrophages and T cells,42 have been identified in early AV lesions,43 and inflammatory activity, visualized by positron emission tomography imaging, has been documented in patients with even mild stenosis 44. This lipid deposition has also been associated with increased angiotensin‐converting enzyme activity in the valve, with profibrotic effects 45. Furthermore, valvular interstitial cells can exhibit osteoblast‐like activity, thus leading to calcific deposition and valvular calcification over time 46.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoproteins and inflammatory cells, such as macrophages and T cells,42 have been identified in early AV lesions,43 and inflammatory activity, visualized by positron emission tomography imaging, has been documented in patients with even mild stenosis 44. This lipid deposition has also been associated with increased angiotensin‐converting enzyme activity in the valve, with profibrotic effects 45. Furthermore, valvular interstitial cells can exhibit osteoblast‐like activity, thus leading to calcific deposition and valvular calcification over time 46.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that ACE and angiotensin II type 1 receptor were upregulated when angiotensin II was expressed in the calcified human aortic valve compared with the normal valve. 21,22 An experimental study showed that in hypercholesterolemic rabbits, ARBs prevented lesion formation in the aortic valve, specifically preventing the accumulation of macrophages, myofibroblasts and osteoblasts, upregulation of osteopontin and ACE, and disruption of endothelial integrity. 23 Findings from these earlier studies and this study suggest that ARBs prevent progression of CAVD during the early stage.…”
Section: Prognostic Factors For Progression Of Early-stage Cavdmentioning
confidence: 99%
“…59,60 A subset of aortic valve lesion macrophages express ACE. 19,20 Surprisingly, a large proportion of valve lesion ACE colocalizes with LDL in the extracellular matrix. 19 Ang II also is localized to these regions, suggesting that the LDL-associated ACE is enzymatically active.…”
mentioning
confidence: 99%